The perspectives of injection drug users regarding safer injecting education delivered through a supervised injecting facility - Fast, Danya (BioMed Central, 2008)
BACKGROUND: Unsafe injection practices are prevalent among injection drug users (IDU) and have resulted in numerous forms of drug-related harm including HIV/HCV transmission and other bacterial and viral infections. North America's first supervised injection facility (SIF) was established in Vancouver in order to address injection-related harms among IDU. This study sought to examine injection drug users' experiences receiving safer injecting education in the context of a SIF. METHODS: Semi-structured qualitative interviews were conducted with 50 individuals recruited from a cohort of SIF users known as the Scientific Evaluation of Supervised Injection (SEOSI) cohort. Audio recorded interviews elicited IDU perspectives regarding the provision of safer injecting education within the context of a SIF. Interviews were transcribed verbatim and a thematic analysis was conducted. RESULTS: Participant narratives indicate that significant gaps in knowledge regarding safer injecting practices exist among local IDU, and that these knowledge deficits result in unsafe injecting practices and negative health outcomes. However, IDU perspectives reveal that the SIF allows clients to identify and address these gaps in knowledge through a number of mechanisms that are unique to this facility, including targeted educational messaging that occurs as a part of the drug use cycle and not outside of it, in situ demonstration of safer injecting techniques that takes place the moment a client is experiencing difficulties, and enhanced opportunities to seek help from 'expert' healthcare professionals. Importantly, study participants indicated that the overall environment of the SIF promotes the adoption of safer injecting practices over time, both within and outside of the facility. CONCLUSION: We conclude that the SIF has been particularly effective in transmitting educational messages targeting unsafe and unhygienic injection practices to a population of active IDU. Consistent with previous work, results of this study indicate that SIFs represent a unique 'micro-environment' that can facilitate the reduction of numerous drug related harms.